Статистичний аналіз стану небанківського фінансового сектору України в умовах воєнного стану - Бачо Роберт; Robert Bacho; Bacsó Róbert; Сочка Катерина; Sochka Kateryna; Szocska Katalin; Потокі Габор; Gabor Pataki; Pataki Gábor (ФОП Кошовий Богдан-Петро Олегович, 2025)
Резюме. У статті досліджено сучасний стан та основні тенденції розвитку небанківського фінансового сектору України в умовах воєнного стану. Метою дослідження є визначення структурних змін, викликів і перспектив функціонування небанківських фінансових установ у кризовий період, а також обґрунтування напрямів посилення їхньої фінансової стійкості та ролі у післявоєнному відновленні економіки. Основні результати полягають у виявленні тенденцій до скорочення кількості небанківських установ (на понад 50%), при одночасному зростанні загального обсягу їх активів на 35,1%. У структурі сектору посилюється домінування фінансових компаній, тоді як питома вага кредитних спілок і ломбардів знижується. Встановлено, що небанківські установи відіграють ключову роль у забезпеченні фінансової доступності для малого бізнесу та населення, особливо у регіонах, де банківська система обмежена. У висновках обґрунтовано необхідність державної підтримки, адаптивного регулювання, цифрової трансформації та інтеграції небанківського сектору в стратегії економічного відновлення України. Запропоновано напрями удосконалення політики нагляду, зміцнення платоспроможності та розширення функцій небанківських установ у післякризовий період.

Abstract. The article examines the current state and key development trends ofUkraine’s non-bank financial sector under martial law. The purpose of the study is toidentify structural changes, challenges, and prospects for the functioning of non-bankfinancial institutions during the crisis, as well as to substantiate directions forstrengthening their financial resilience and role in the post-war recovery of thenational economy.The research applies methods of comparative statistical analysis, time seriesanalysis, structural evaluation, and regulatory generalization, which enabled acomprehensive assessment of quantitative and qualitative transformations in the non-bank sector over the period 2021–2024. The empirical base consists of official reportsfrom the National Bank of Ukraine, data from international institutions, and relevantacademic literature.The main findings highlight a more than 50% reduction in the number of non-bank institutions, alongside a 35.1% increase in their total assets. The structure of thesector is shifting toward the dominance of financial companies, while the share ofcredit unions and pawnshops is declining. Non-bank institutions play a crucial role in ensuring financial accessibility for small businesses and households, especially inregions where traditional banking services are limited due to wartime constraints.The conclusions justify the need for state support, adaptive regulation, digitaltransformation, and deeper integration of the non-bank financial sector into Ukraine’seconomic recovery strategy. Policy recommendations include strengtheningsupervisory practices, improving solvency, and expanding the functional scope of non-bank institutions in the post-crisis period.
Statistical analysis of the state of the non-banking financial sector of Ukraine under martial law
https://a-economics.com.ua/index.php/home/issue/view/11
Keywords: небанківський фінансовий сектор; воєнний стан; фінансова стійкість; кредитні спілки; страхові компанії